Pyrearinus termitilluminans larval click beetle luciferase: Active site properties, structure and function relationships and comparison with other beetle luciferases - Silva Neto, A. J. [UNESP]; Scorsato, V.; Arnoldi, F. G C; Viviani, V. R. (Springer Nature, 2009)
Several beetle luciferases have been cloned and sequenced. However, most studies on structure and function relationships and bioanalytical applications were done with firefly luciferases, which are pH sensitive. Several years ago we cloned Pyrearinus termitilluminans larval click beetle luciferase, which displays the most blue-shifted bioluminescence among beetle luciferases and is pH insensitive. This enzyme was expressed in E. coli, purified, and its properties investigated. This luciferase shows slower luminescence kinetics, KM values comparable to other beetle luciferases and high catalytic constant. Fluorescence studies with 8-anilino-1-naphtalene-sulfonic acid (1,8-ANS) and modeling studies suggest that the luciferin binding site of this luciferase is very hydrophobic, supporting the solvent and orientation polarizability effects as determining mechanisms for bioluminescence colors. Although pH insensitive in the range between pH 6-8, at pH 10 this luciferase displays a remarkable red-shift and broadening of the bioluminescence spectrum. Modeling studies suggest that the residue C312 may play an important role in bioluminescence color modulation. Compared to other beetle luciferases, Pyrearinus termitilluminans luciferase also displays higher thermostability and sustained luminescence in a bacterial cell environment, which makes this luciferase particularly suitable for in vivo cell analysis and bioimaging. © The Royal Society of Chemistry and Owner Societies 2009.
Keywords: Amino Acid Sequence; Animals; Beetles; Catalytic Domain; Kinetics; Luciferases; Molecular Sequence Data; Protein Structure, Tertiary; Recombinant Proteins; Sequence Alignment; Sequence Homology, Amino Acid; Temperature; Bacteria (microorganisms); Coleoptera; Elateridae; Pyrearinus termitilluminans